Age-related pattern of the antiepileptic drug utilization in active epilepsy : a population-based survey - Bielen, Ivan (Array, 2009)
Abstract: The aim of this study was to investigate the relationship between antiepileptic drug (AED) utilization and patient age in a population of patients treated by primary health care physicians. Data were collected by using questionnaires completed by family physicians and paediatricians working in primary health care. Only patients with active epilepsy confirmed previously by neurologists or neuropaediatricans were included. One hundred and twenty-three physicians provided the requested data for 966 patients (range 1–92 years). Most frequently prescribed AEDs were barbiturates (BARB) (37%) and carbamazepine (CBZ) (37%). Valproic acid derivates (VPA) were prescribed in 28%, but the rate was higher (51%) in children. By calculating the correlation between age and the prescription of single AEDs across the whole sample, linear correlations were found for BARB (r=0.94; p<0.01), VPA (r=–0.93; p<0.01) and for topiramate (TPM) (r= –0.90; p<0.01). Since our results showed significant correlations between age and the use of the majority of AEDs, we concluded that the age may be considered a methodological bias in the presentation of data. Therefore we calculated AED utilization as the age-adjusted prevalence rates (per/1000 inhabitants). For the most commonly prescribed AEDs they were: BARB 1.8 (95% CI 1.6–2.0), CBZ 1.9 (95% CI 1.7–2.1), VPA 1.3 (95% CI 1.1–1.5), lamotrigine (LTG) 0.7 (CI 95% 0.6–0.8), TPM 0.6 (CI 95% 0.5–0.7). In conclusion, the age of patients has a significant impact on the prescription patterns not only between children and adults, but at every age. Therefore we suggest that reporting of AED utilization pattern should also include age-standardized prevalence rates of individual AED utilization